The Strategy Of Puri Agung Tabanan As A Cultural Center (International Journal of Interreligious and Intercultural Studies, 2024)
A Balinese culture is a form of culture in which every system of ideas, and social system to its physical manifestation in totality is based on values derived from Hinduism. Puri with its cultural resources still upholds the values of local wisdom of a region and represents the cultural and spiritual roots of Bali. In recent decades, puri as one of the elements of Balinese culture has been faced with various serious problems related to the existence of puri as a cultural center.This research aims to examine the existence of Puri Agung Tabanan as a cultural center. Based on this, the researchers formulated three problems, namely:  Why is Puri Agung Tabanan declared as a cultural center? What is the strategy of Puri Agung Tabanan as a cultural center? What are the implications of Puri Agung Tabanan as a cultural center for the existence of Balinese culture, the puri, and the surrounding community? This research uses a qualitative approach method, with descriptive analysis. Data collection techniques were observation, in-depth interviews, and document studies. Informants were collected through a purposive sampling technique. The research location is Puri Agung Tabanan located in Banjar Dinas Sakenan Baleran, Delod Peken Village, Tabanan District, precisely on Jalan Srigunting No. 3, Tabanan, Bali.Formally, puri as the center of power is gone, but puri is symbolic. Puri’s strategy is to maintain its existence as a cultural center through acculturation or socialization strategy. The explanation model of Puri Agung Tabanan as a cultural center is a form of articulation that the function of the puri as the center of inheritance and preservation of Balinese culture remains relevant in the future. The existence of puri as a cultural center is a form of the birth of a new civilization milestone created by the current generation to represent the Balinese people, especially in Tabanan Regency in building a spirit based on a system of cultural values that already exists in the relationship of community life towards Bali New Era 100 years ahead (2025 to 2125).